Safety Culture Development in Future Preschool and Primary Education Specialists in the Conditions of Martial Law in Ukraine - Yankovych, Oleksandra; Zharkova , Iryna; Kuzma, Iryna; Chaikovska , Hanna; Binytska, Kateryna (Journal of Education Culture and Society, 2025)
Thesis. The aim of the research is to substantiate and experimentally test the model of safety culture development in future specialists of preschool and primary education in the conditions of martial law in Ukraine.Concept. The main idea of the experimental model is to explore life safety issues in connection with the reflection of safety and danger issues in the history of Ukraine, oral folk art, literature, art, religion, preschool and primary school pedagogy. Safety culture development is influenced by national, informational, legal, media culture, the culture of peace, health, etc. This process is interconnected and safety culture affects the development of these various cultures.Results and Conclusion. The safety culture structure has been clarified. A diagnostic toolkit for determining its development level in students (future primary school teachers and educators) has been revealed. An experimental model of safety culture development has been formed as an open system, the components of which are the aim; safety culture structure; algorithm of actions; main areas of work; forms and methods of safety culture development, including integrated classes, storytelling on safety and danger topics, game activities; as well as diagnostic toolkit and results. This encompasses integrated classes, storytelling on safety and danger topics, game activities.